Institutions and Mobilization: Explaining and Understanding the Intersection - Adewale, Olugbenga; Ogunbanjo, Bimbo (Al-Adab Journal, 2025)
This paper highlights how institutions often shape the paths available for political involvement. Many formal, lawful, and effective institutional avenues for people to express their aspirations are associated with significant extra-institutional action; this is one of the most significant conclusions drawn from the mobilization literature. With institutions serving as the independent variable, most scholarly studies have concentrated on how institutions affect mobilization. There is also a smaller body of study that examines the effects of mobilization on formal institutions, particularly about party politics, voting processes, and legal frameworks. Additionally, a large number of academics have examined institutions inside movements as well as movements within institutions as worthwhile areas of study. This paper identifies fourteen consensus propositions about the connections between institutions and mobilization. Although these fourteen conclusions are frequently taken for granted, further empirical testing is necessary to assess their robustness over a larger number of situations and historical periods. For this reason, they are given as testable hypotheses. The next section outlines three main obstacles to determining more widespread causal patterns: (1) a conceptual ambiguity in defining pertinent "institutions" as study subjects; (2) a dearth of worldwide data on protest and mobilization that could produce empirical findings that are broadly applicable; and (3) a historical propensity to extrapolate conclusions from a limited number of Western cases. To improve our collective grasp of the links between these notions, a few substantive and methodological approaches are suggested in the paper's conclusion.